Diagnostic performance of triple-phase computed tomography in the evaluation of hepatocellular carcinoma / Noor Hanisah Mohamad Tarmizi, Fara Shuhaida Shafiee and Mohd Hafizi Mahmud - Mahmud, Mohd Hafizi; Mohamad Tarmizi, Noor Hanisah; Shafiee, Fara Shuhaida (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The study aimed to evaluate the diagnostic performance of triple- phase CT imaging of liver for the evaluation of hepatocellular carcinoma (HCC) patients with cirrhosis and/or chronic liver disease. 39 radiological reports of patient who had undergone triple- phase contrast-enhanced CT liver study for suspected/known HCC from January 2016 to December 2018 were reviewed. The findings were validated with serum alpha-fetoprotein (AFP) levels concentration to confirm the malignancy of the HCC. The sensitivity, specificity, predictive values and diagnostic accuracy of the triple-phase CT were determined using ROC curve analysis. The HU cut-off value in triple-phase CT was further estimated for discrimination between benign (non-HCC nodule) and malignant (HCC nodule) hepatic lesion. Positive results of 20 HCC lesions and negative results of 19 non-HCC lesions were observed. Triple-phase CT imaging has a sensitivity and specificity of 85% and 94.7% (p <0.001), respectively with 94.4% PPV and 85.7% NPV with the overall diagnostic accuracy of 89.7%. The optimal cut-off values of 43 HU at arterial phase, 50.5 HU at portal venous phase and 46 HU at delayed phase were proposed for discrimination between benign (non-HCC nodule) and malignant (HCC nodule) hepatic lesion. Triple-phase CT with high accuracy is helpful for the evaluation of hepatocellular carcinoma. It has indispensable role in characterizing and differentiating benign and malignant hepatic lesion, hence this protocol could further improve the clinical management of patients with cirrhosis and/or chronic liver disease.